2021
DOI: 10.3390/jcm10194291
|View full text |Cite
|
Sign up to set email alerts
|

Experience with a Hybrid Procedure Involving Laparoscopic Fundoplication with Percutaneous Endoscopic Gastrostomy in Chronically Ill Children

Abstract: Gastrostomy with concurrent laparoscopic Nissen fundoplication (LNF) is often performed as a laparoscopic gastrostomy (LG) by surgeons. Since 2014, we started performing percutaneous endoscopic gastrostomy (PEG) as gastrostomy with LNF. This study aims to compare the outcomes of LG and PEG with LNF. Patients were recruited into two groups: LNF with LG (historical control) or PEG. Demographic data, operation time, time to start feeding, time to full feeding, length of hospital stay (LOS), and complications were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Therefore, a recent study published in Korea reported that concomitant EGD during fundoplication was better than fundoplication alone regarding optimal tightness inside the esophagus. 16 …”
Section: Discussionmentioning
confidence: 99%
“…Therefore, a recent study published in Korea reported that concomitant EGD during fundoplication was better than fundoplication alone regarding optimal tightness inside the esophagus. 16 …”
Section: Discussionmentioning
confidence: 99%